A comparative analysis of urine trypsinogen-2 test strip with serum lipase in diagnosis of acute pancreatitis in emergency set-up - Mishra, Jagmohan; Mishra, Biplab; Firodous, Afroza (International Surgery Journal, 2018)
Background: Acute pancreatitis possess difficulty in diagnosis in its emergency presentation. Hence to segregate this disease is important from other specific or non-specific causes of acute abdomen. Hence in suspected cases in majority of patients the urinary trypsinogen-2 test strip (Actim pancreatitis) can be used to detect this disease, especially in emergency set-up. The result of the strip test is then corroborated with findings of serum lipase in the blood. Methods: Author prospectively compared 205 consecutive patients with acute abdominal pain admitted to the casualty, SCB Medical College and Hospital. The patients were tested on admission with the Actim pancreatitis test strip. Serum amylase, serum lipase, and urine trypsinogen-2 concentrations were also determined quantitatively. Results: The Actim pancreatitis test strip was sensitive in 93% cases and specific in 92% cases. This was superior to that of serum lipase (sensitivity 77% and specificity 87%). With a cut-off >3x the upper reference limit, the sensitivity of serum lipase was only 52% while the specificity was 98%. The high sensitivity for the Actim pancreatitis test strip resulted in every high negative predictive value of 99%. Conclusions: In patients with acute abdominal pain seen in emergency department, a negative dipstick for urinary trypsinogen-2 rules out acute pancreatitis with high degree of probability and therefore appears to be more suitable for screening of acute pancreatitis. With its high specificity with a cut-off >3x the upper reference limit, serum lipase is suitable as a confirmatory test for pancreatitis when a positive dipstick result is obtained.